2022
DOI: 10.1371/journal.pone.0263264
|View full text |Cite
|
Sign up to set email alerts
|

Development of a computerized intervention to improve health literacy in older Hispanics with type 2 diabetes using a pharmacist supervised comprehensive medication management

Abstract: Objective The primary objective was to develop a computerized culturally adapted health literacy intervention for older Hispanics with type 2 diabetes (T2D). Secondary objectives were to assess the usability and acceptability of the intervention by older Hispanics with T2D and clinical pharmacists providing comprehensive medication management (CMM). Materials and methods The study occurred in three phases. During phase I, an integration approach (i.e., quantitative assessments, qualitative interviews) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In our study, health literacy was not only associated with medication adherence but also identified as a mediator of the relationship between social support and medication adherence, indicating that health literacy may serve as a core determinant of medication adherence among patients with hypertension. Improving health literacy has been suggested as a possible intervention target to increase medication adherence [ 41 , 43 ] as well as other hypertension self-care behaviors [ 42 , 44 ]. Although health literacy has a positive impact on medication adherence in patients with hypertension, little is known about the mechanism of this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, health literacy was not only associated with medication adherence but also identified as a mediator of the relationship between social support and medication adherence, indicating that health literacy may serve as a core determinant of medication adherence among patients with hypertension. Improving health literacy has been suggested as a possible intervention target to increase medication adherence [ 41 , 43 ] as well as other hypertension self-care behaviors [ 42 , 44 ]. Although health literacy has a positive impact on medication adherence in patients with hypertension, little is known about the mechanism of this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study revealed that health literacy was negatively related to SUA level. A Study found that enhancing health literacy has been considered a possible intervention target to improve patients' self-care behaviors [37]. A study demonstrated that health literacy signi cantly and positively correlated with physical exercise, diet, and sleep [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate health literacy is one of the main factors leading to poor medication adherence in patients with hypertension ( 46 , 76 ). Therefore, improving health literacy has been suggested as an effective measure for improving medication adherence ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%